2019
DOI: 10.3389/fphar.2019.00352
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cannabidiol Prevents Allodynia and Neurological Dysfunctions in a Mouse Model of Mild Traumatic Brain Injury

Abstract: Neurological dysfunctions are the most impactful and persistent consequences of traumatic brain injury (TBI). Indeed, previous reports suggest that an association between TBI and chronic pain syndromes, as well anxio-depressive behaviors, tends to be more common in patients with mild forms of TBI. At present, no effective treatment options are available for these symptoms. In the present study, we used a weight drop mild TBI mouse model to investigate the effect of a commercially available 10% Cannabidiol (CBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 32 publications
1
41
0
2
Order By: Relevance
“…Similar to human studies, CBD did not produce complete analgesia in all models of chronic pain; in a cisplatin-induced mouse model of neuropathy, CBD attenuated but did not prevent hyperalgesia (Harris et al, 2016). Mechanical hyperalgesia was improved by CBD treatment following traumatic brain injury in mice, myofascial pain in rats, and 6-hydroxydopamine-induced mouse model of Parkinson's disease, however these studies require follow-up to inspect potential mechanisms of action (Belardo et al, 2019;Wong and Cairns, 2019;Crivelaro Do Nascimento et al, 2020). The preclinical work being done to disentangle the mechanisms of CBD in providing analgesic support in chronic pain is flourishing, but much remains in the wake of chronic disease and enhancing our understanding of the mechanisms at play.…”
Section: Mechanistic Insights For Cannabidiol Treatment Of Chronic Painmentioning
confidence: 78%
“…Similar to human studies, CBD did not produce complete analgesia in all models of chronic pain; in a cisplatin-induced mouse model of neuropathy, CBD attenuated but did not prevent hyperalgesia (Harris et al, 2016). Mechanical hyperalgesia was improved by CBD treatment following traumatic brain injury in mice, myofascial pain in rats, and 6-hydroxydopamine-induced mouse model of Parkinson's disease, however these studies require follow-up to inspect potential mechanisms of action (Belardo et al, 2019;Wong and Cairns, 2019;Crivelaro Do Nascimento et al, 2020). The preclinical work being done to disentangle the mechanisms of CBD in providing analgesic support in chronic pain is flourishing, but much remains in the wake of chronic disease and enhancing our understanding of the mechanisms at play.…”
Section: Mechanistic Insights For Cannabidiol Treatment Of Chronic Painmentioning
confidence: 78%
“…Specifically, CBD tended to normalise extracellular glutamate, D-aspartate, and γ-aminobutyric acid concentrations in the medial prefrontal cortex, suggesting a reduction in excitotoxicity. However, neuronal damage was not measured directly in this study [14].…”
Section: Neuroprotection-concussion and Subconcussionmentioning
confidence: 87%
“…While the primary injury may not be treatable, interventions that attenuate secondary sequelae are likely to be of benefit [203]. Only one study [14] has investigated the biochemical and neuropsychological effects of CBD in an animal model of TBI. Here, C57BL/6 mice were given chronic CBD treatment (3 μg•day −1 , oral) 1-14 and 50-60 days post-(weight drop) brain insult.…”
Section: Neuroprotection-concussion and Subconcussionmentioning
confidence: 99%
“…Our behavioral experiments were carried a day after the exposure to pilocarpine and two days after mTBI induction. Previous reports indicated that mTBI mice develop long term neuropsychiatric condition of increased anxiety and later depression (Guida et al, 2017;Belardo et al, 2019). In this sense, could a bigger time lag from the seizures restore the hippocampal abilities of the mTBI treated animals?…”
Section: Discussionmentioning
confidence: 98%